ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE APLIKASI MOBILE BAHANA DXTRADE DENGAN METODE SYSTEM USABILITY SCALE - Fabian Abi Pratama, (2023)
PT Bahana Sekuritas is a company engaged in the capital market industry as an underwriter and securities broker which was founded in 1993. The mobile application is one of the media used by PT Bahana Sekuritas to serve retail customers so they can invest in securities products, especially stocks through PT Bahana Sekuritas. Therefore, optimizing the mobile application is important to ensure that the purpose of using this mobile application is in accordance with customer needs. This study aims to provide an assessment of the user experience and redesign the interface that is able to meet the usability level of the Bahana DXtrade mobile application using the User Centered Design (UCD) approach. The application of the UCD method is carried out by carrying out questionnaires and prototyping with the System Usability Scale testing technique. This research will produce a new interface display solution in the form of a prototype that can be used as a suggestion for improving the appearance of the Bahana DXtrade mobile application. In the analysis of the interface display on the existing system, after testing using the System Usability Scale method for the Bahana DXtrade mobile application, an average score of 52 was obtained, which means that the usability and usability value of the Bahana DXtrade mobile application cannot be said to be acceptable. After the redesign process was carried out by applying the User Centered Design approach and re-testing the prototype resulting from the redesign of the interface display using the System Usability Scale, it was found that the average score increased to 76 or can be said to be successful or acceptable.